2010
DOI: 10.22146/ijc.21891
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Activation of Natural Zeolit From Ponorogo

Abstract: Characterization and activation of Natural Zeolite from Ponorogo (ZAP) have been done to improve the quality of zeolite as porous material. Analysis of mineral composition is done using X-Ray Difraction (XRD), Fourier Transform-Infra Red (FTIR) Spectroscopy and metal analysis using Atomic Absorption Spectroscopy (AAS). Characterization of the activated zeolite covered about number of acidic sites, surface area, ratio Si/Al and metal composition (Na, Ca, K and Fe). Activated processes is done using various mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 1 publication
0
12
0
4
Order By: Relevance
“…The change of the Si/Al ratio in zeolite will have an impact on its ability as a catalyst. Heraldy et al [16] reported that activation of natural zeolite from Ponorogo-Indonesia using HCl could increase the Si/Al ratio from 3.95 to 4.78. Similarly, an increased in Si/Al ratio compounds.…”
Section: Characterization Of Catalystmentioning
confidence: 99%
See 2 more Smart Citations
“…The change of the Si/Al ratio in zeolite will have an impact on its ability as a catalyst. Heraldy et al [16] reported that activation of natural zeolite from Ponorogo-Indonesia using HCl could increase the Si/Al ratio from 3.95 to 4.78. Similarly, an increased in Si/Al ratio compounds.…”
Section: Characterization Of Catalystmentioning
confidence: 99%
“…The Si/Al ratio tends to increase along the presence of acid or base from the zeolite activation. On the other hand, KZ-HCl-1 zeolite has the highest Si/Al ratio, which was probably the result of dealumination caused by the presence of HCl as an activating agent [16,24]. When NaOH was used as an activating agent, it caused silica dissolution that lead to changes in the zeolite structure, reducing the silica content in the zeolite framework and thus, decreasing the Si/Al ratio.…”
Section: Characterization Of Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher temperature will be increased the molecular kinetic energy, and the adsorption balance will be moved towards desorption. Therefore, a higher temperature can reduce the performance of the catalyst [17]. However, as shown in Figure 3 indicates if the addition of catalyst greater than 15%, the yield of coal oil will increase.…”
Section: Effects Of Catalyst Weight Addition On Coal Oil Yield At Temmentioning
confidence: 99%
“…Peningkatan keasaman zeolit mampu memperbesar kemampuan penyerapan zeolit. Hal itu terjadi karena banyaknya pori-pori zeolit yang terbuka dan permukaan padatannya menjadi bersih dan luas (Heraldy, et al, 2003).…”
Section: µM µM µM µM µMunclassified